RELATIONSHIPS BETWEEN PHYSICAL FITNESS AND MORPHOLOGICAL CHARACTERISTICS IN OBESE EIGHT-YEAR-OLD CHILDREN: A CROSS-SECTIONAL STUDY - Živković Danijela,; Đošić Anđela, (Sport Scientific And Practical Aspects, 2025)
The objective of this study was to investigate the association between Physical Fitness (PF) parameters and morphological features in eight-year-old obese children. The sample consisted of 273 obese second-grade students from Niš, Serbia (104 girls and 169 boys; mean age 8.26 ± 0.40 for girls and 8.34 ± 0.43 for boys). The assessed PF parameters included Resting Heart Rate (RHR), Exercise Heart Rate (EHR), maximal oxygen uptake (VO₂max), and a battery of tests measuring strength, flexibility and speed. Morphological characteristics were evaluated using 13 variables encompassing longitudinal, transversal, and volumetric dimensions, as well as skinfold thickness measurements. Canonical correlation analysis was conducted to examine the relationships between sets of fitness-related and morphological variables. The results revealed three statistically significant canonical functions, reflecting complex interrelationships between PF parameters and body structure. The first canonical function (Sig.= .00) demonstrated negative correlation between VO₂max and obesity-related parameters. The second function (Sig.= .00) reflects the relationship between longitudinal body dimensions and the ability to perform fast, alternating upper limb movements. The third function (Sig.= .04) suggested that children with more pronounced longitudinal body dimensions, but also with higher levels of subcutaneous fat, tend to achieve better results in tests of explosive strength and flexibility. These findings emphasize the complex and multidimensional relationship between physical fitness and morphological characteristics in eight-year-old children. They underscore the importance of early identification and the implementation of targeted, school-based interventions aimed at promoting health and supporting optimal physical development in young children.